Backgrounds of development of sports-oriented technology of physical health of students in higher education staff - Globa, T.; Zaharina, Ye. (Journal of Education, Health and Sport, 2017)
The preconditions of development of sports-oriented technology of physical education of students of institutions of higher education for the modernization and increase of the efficiency of the process of physical education in higher education institutions are determined. An expert evaluation was carried out on the method of advantage (ranking) (as experts were involved 15 heads of departments of physical education institutions of higher education in different regions of Ukraine). The factors that reduce the efficiency of physical education of students are determined. Systematization of the material made it possible to find out that in the institutions of higher education there are proper conditions (organizational, material and technical, personnel) for the organization of sports-oriented classes, at the same time, the programmatic and methodological support of this activity needs additional attention due to insufficient theoretical substantiation and inappropriate the effectiveness of existing developments.